2001
DOI: 10.1136/fn.85.2.f86
|View full text |Cite
|
Sign up to set email alerts
|

A randomised control study comparing the Infant Flow Driver with nasal continuous positive airway pressure in preterm infants

Abstract: Objective-To compare the eVectiveness of the Infant Flow Driver (IFD) with single prong nasal continuous positive airway pressure (nCPAP) in preterm neonates aVected by respiratory distress syndrome. Design-Randomised controlled study. Patients-Between September 1997 and March 1999, 36 preterm infants who were eligible for CPAP treatment were randomly selected for either nCPAP or IFD and studied prospectively for changes in oxygen requirement and/or respiratory rate. The requirement for mechanical ventilation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 15 publications
0
53
0
2
Order By: Relevance
“…The short-term benefits of the variable-flow NCPAP delivery systems over continuous-flow infant ventilator delivery have been demonstrated in several studies; preterm infants supported for short periods of time with variable-flow NCPAP systems have increases in V T and lung volume and decreases in FiO 2 and both inspiratory and resistive work of breathing when compared to continuous-flow NCPAP delivery. 18,26,27 Although the water seal bubble CPAP system employed in other reports of preferential early NCPAP has theoretical advantages in lung recruitment and differential effects in response to variable lung compliance, 17 varying the degree of oscillation does not alter short-term oxygenation or ventilation in preterm infants. 28 Further, no differential effects on lung mechanics were demonstrated after short-term support of preterm infants with the variable-flow system compared to the water seal bubble system, except for slightly lower respiratory rates and resistive work of breathing during variable-flow NCPAP support.…”
Section: Discussionmentioning
confidence: 99%
“…The short-term benefits of the variable-flow NCPAP delivery systems over continuous-flow infant ventilator delivery have been demonstrated in several studies; preterm infants supported for short periods of time with variable-flow NCPAP systems have increases in V T and lung volume and decreases in FiO 2 and both inspiratory and resistive work of breathing when compared to continuous-flow NCPAP delivery. 18,26,27 Although the water seal bubble CPAP system employed in other reports of preferential early NCPAP has theoretical advantages in lung recruitment and differential effects in response to variable lung compliance, 17 varying the degree of oscillation does not alter short-term oxygenation or ventilation in preterm infants. 28 Further, no differential effects on lung mechanics were demonstrated after short-term support of preterm infants with the variable-flow system compared to the water seal bubble system, except for slightly lower respiratory rates and resistive work of breathing during variable-flow NCPAP support.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 IF-CPAP has been shown to decrease oxygen requirement, improve respiratory effort [6][7][8][9] and prevent extubation failure in preterm infants when compared to traditional nasal prong systems and bubble CPAP. 9,10 However, nasal prong CPAP devices have been shown to damage the nares of infants, causing discomfort and rarely, long-term disfigurement. 11,12 Simple nasal cannula has recently been shown to generate positive end-expiratory pressure (PEEP) in preterm infants if air or oxygen is delivered at a high flow rate (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies demonstrated that it contributes to a reduction in the need and dependence of oxygen and respiratory rate as well as the need for mechanical ventilation [1][2].…”
Section: Introductionmentioning
confidence: 99%